2020
DOI: 10.1038/s41398-020-00884-5
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal sevoflurane exposure induces impulsive behavioral deficit through disrupting excitatory neurons in the medial prefrontal cortex in mice

Abstract: Sevoflurane, in particular multiple exposures, has been reported to cause the abnormal neurological development including attention-deficit/hyperactivity disorder (ADHD). This study is to investigate ADHD-like impulsivity in adult mice after repeated sevoflurane exposures at the neonatal stage. Six-day-old pups were exposed to 60% oxygen in the presence or absence of 3% sevoflurane for 2 h and the treatment was administrated once daily for three consecutive days. To assess the impulsivity, the cliff avoidance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 45 publications
(49 reference statements)
0
23
0
Order By: Relevance
“…The level of neuronal activity in aged mice, however, was overtly increased, exceeding the baseline for at least 24 h. As neuronal activity is important for learning and memory, this dysregulation of Ca 2+ activity in the frontal cortex may contribute to post‐anesthesia cognitive impairment. Interestingly, similar to aged animals, neonatal rodents exposed to sevoflurane anesthesia also exhibited an increase in ER stress‐related proteins and neuronal hyperactivity (Shen et al, 2018; Xie et al, 2020; Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of neuronal activity in aged mice, however, was overtly increased, exceeding the baseline for at least 24 h. As neuronal activity is important for learning and memory, this dysregulation of Ca 2+ activity in the frontal cortex may contribute to post‐anesthesia cognitive impairment. Interestingly, similar to aged animals, neonatal rodents exposed to sevoflurane anesthesia also exhibited an increase in ER stress‐related proteins and neuronal hyperactivity (Shen et al, 2018; Xie et al, 2020; Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of preclinical studies suggest that prolonged exposure to general anesthesia can induce delirium‐like behavior, including cognitive impairment, as well as molecular and cellular changes characteristic of neurodegeneration such as endoplasmic reticulum (ER) stress, tau hyperphosphorylation, neuroinflammation, and cell death (Vutskits & Xie, 2016). For example, young mice repeatedly exposed to sevoflurane, a widely used inhalational anesthetic, exhibit abnormal social and impulsive behavior, deficits in motor learning, and impairments in fear and spatial memory (Le Freche et al, 2012; Satomoto et al, 2009; Xie et al, 2020; Yu et al, 2020). In neonatal rodents, exposure to sevoflurane causes a transient increase in neuronal activity, rapid changes of dendritic spine density, and elevation of tau protein phosphorylation and interleukin‐6 expression in the brain (Dong et al, 2021; Lu et al, 2017; Tao et al, 2014; Yang et al, 2020; Yu et al, 2020; Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The PFC has extensive reciprocal connections with wakepromoting centers in the brainstem and diencephalon (Briand et al, 2007;Pal et al, 2018); indeed, cholinergic stimulation of the PFC can restore wake-like behavior following sevoflurane anesthesia (Pal et al, 2018). Sevoflurane exposure has been shown to induce behavioral deficits, poor memory performance, and neurofunctional abnormalities by disrupting excitatory neurons in the PFC (Xu et al, 2018;Xie et al, 2020;Zhao et al, 2020). Our previous study found that sevoflurane-induced impairment in m6A-mediated mRNA translation in the PFC was related to fine motor deficits (Zhang L. et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sevoflurane, a volatile anesthetic agent, can disrupt consciousness and cognition. It has also been shown to lead to synaptic and myelin damage, neuroinflammation, excitatory neuron abnormality, and neuronal apoptosis in the brains of young animals (Xie et al, 2020;Zhao et al, 2020). To explore the molecular mechanism underlying anesthesia and sevoflurane-induced deficiencies, a number of transcriptome studies using RNA sequencing (RNA-seq) techniques have been conducted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation